Mathematical communication ability of 7th grade Junior High School students by using Knisley’s model assisted by textbook supplements - Putri, Dian Kartika; Rochmad, Rochmad (Department of Mathematics, Universitas Negeri Semarang, 2021)
Mathematical communication ability needs to be improved so that students can solve math problems well. This study aims to determine the effectiveness of Knisley’s learning model assisted by textbook supplements on achieving mathematical communication ability. The type of this research was quantitative method research with a Quasi-Experimental design. The population was the students of class VII A, and VII B at SMP Muhammadiyah Pangkalan Bun Kalimantan year 2019/2020. Data collection techniques used are tests. The results showed that Knisley’s learning model assisted by textbook supplement is effective in achieving students’ mathematical communication ability, namely (1) the proportion of student’s mathematical communication ability reaches more than 75% classical completeness, and (2) the average test results of the students’ mathematical communication ability who follow Knisley’s learning model assisted by the textbook supplement are better than the students’ mathematical communication ability who follow Knisley’s learning model without textbook supplement.